Broad-band negative refraction via simultaneous multi-electron transitions. (23rd January 2019) - Cheng, Jing-Jing; Chu, Ying-Qi; Liu, Tao; Zhao, Jie-Xing; Deng, Fu-Guo; Ai, Qing; Nori, Franco
Abstract: The potential applications of metamaterials with negative refraction are limited by their narrow bandwidth and difficulty in fabrication. In order to broaden the bandwidth, we analyze different factors which influence the negative refraction in solids and multi-atom molecules. We find that this negative refraction can be significantly enhanced by simultaneous multi-electron transitions with the same transition frequency and dipole redistribution over different eigenstates. We show that these simultaneous multi-electron transitions and enhanced transition dipole broaden the bandwidth of the negative refraction by at least one order of magnitude . Furthermore, we show the possible application of this scheme in hyperbolic metamaterials using diamonds with NV centers.